2015
DOI: 10.1007/s11255-015-1018-9
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae in health care-associated urinary tract infection: focus on susceptibility to fosfomycin

Abstract: Fosfomycin could be an alternative treatment option for UTIs related to ESBL-producing E. coli spp. and CoA-UTI, but not for UTIs related to ESBL-producing Klebsiella spp. Antimicrobial susceptibilities of ESBL-producing strains were different according to the UTI classification. Fosfomycin showed decreased activity against isolates from HCA-UTI and HA-UTI. However, further clinical verification is required to assess the clinical efficacy of fosfomycin for the treatment of UTIs caused by ESBL-producing E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 31 publications
1
32
1
4
Order By: Relevance
“…Our results are similar, to some extent, to those reported by Jones et al (Jones et al, 2002), Iroha et al(Iroha et al, 2015), Cho et al(Cho et al, 2015), Chen et al(Chen et al, 2015) who found that carbapenems (biapenem, meropenem and imipenem) exhibited high antimicrobial activities against Gram-negative bacteria especially E. coli and Klebsiella pneumoniae. Also Turner examined the activity of meropenem against a total of 5208 isolates of Enterobacteriaceae; the susceptibility rate for meropenem was (99.4%).…”
Section: Resultssupporting
confidence: 92%
“…Our results are similar, to some extent, to those reported by Jones et al (Jones et al, 2002), Iroha et al(Iroha et al, 2015), Cho et al(Cho et al, 2015), Chen et al(Chen et al, 2015) who found that carbapenems (biapenem, meropenem and imipenem) exhibited high antimicrobial activities against Gram-negative bacteria especially E. coli and Klebsiella pneumoniae. Also Turner examined the activity of meropenem against a total of 5208 isolates of Enterobacteriaceae; the susceptibility rate for meropenem was (99.4%).…”
Section: Resultssupporting
confidence: 92%
“…Fosfomycin presented high levels of activity against E. coli. However, this drug was less active against Klebsiella spp., which displayed a higher MIC distribution (21)(22)(23). Falagas et al reported that the fosfomycin MIC distribution can be quite variable and can also be influenced by several factors, including bacterial species (24).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative susceptibility of fosfomycin against ESBL positive Enterobacteriaceae is reported as 87.7% according to CLSI criteria (24). However, lower susceptibility rates (<50%) was showed in some studies, and in a study this agent was shown to be active against only 50% of Klebsiella (22,25).…”
Section: Discussionmentioning
confidence: 99%